A Reconsideration of Alexandrian Christology - Young, Frances M. (The journal of ecclesiastical history, 1971)
In modern Christological thinking, the tendency is to start with an affirmation of the real humanity of Christ. We recognise with everincreasing realism that the man, Jesus, lived a life open to historical investigation, a life which was circumscribed within the limitations of a normal human psychology and its contemporary environment. This being our pre-supposition, we tend to approve the Antiochene school for its realistic exegesis of New Testament texts referring to the human weakness, progress, experience, finite knowledge, temptation and conflict of the Christ. Correspondingly, we criticise the Alexandrian Fathers for their unnatural exegesis, based, we instinctively feel, upon a form of docetism, however sophisticated. How justifiable is this attitude? It is not the purpose of this paper to minimise the difficulties involved in the Alexandrian position, but the following suggestions may lead to a more sympathetic view of Alexandrian thinking.